2023
DOI: 10.1094/pdis-02-22-0309-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Epicoccum sorghinum Causing Leaf Spot on Basella alba in Malaysia

Abstract: Basella alba (family Basellaceae) is a perennial vine that serves as an edible leaf vegetable in Malaysia. In May 2021, red spots were observed on leaf samples of B. alba in Lido, Sabah Province (5°56'39.1"N, 116°04'47.6"E). The disease severity was about 20% with 10% incidence. The spots enlarged and coalesced into larger necrotic spots. Small pieces (5 x 5 mm) of infected leaves were excised from three plants, and then surface disinfected based on Khoo et al. (2022). One fungal isolate (Lido01) was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Leaf spots occur in various plant species, including Nicotiana tabacum (Yuan et al, 2016), Bletilla striata (Zhou et al, 2018), and Brassica parachinensis (Yu et al, 2019), indicating that the pathogen could cause a variety of plant diseases. In addition, the incidence of leaf spot disease caused by this pathogen was 10%–20% in Basella alba (Khoo et al, 2022) and 49%–56% in Camellia sinensis (Bao et al, 2019). Furthermore, Zhao et al (2022) reported that E. sorghinum infected H. macrophylla in Beijing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf spots occur in various plant species, including Nicotiana tabacum (Yuan et al, 2016), Bletilla striata (Zhou et al, 2018), and Brassica parachinensis (Yu et al, 2019), indicating that the pathogen could cause a variety of plant diseases. In addition, the incidence of leaf spot disease caused by this pathogen was 10%–20% in Basella alba (Khoo et al, 2022) and 49%–56% in Camellia sinensis (Bao et al, 2019). Furthermore, Zhao et al (2022) reported that E. sorghinum infected H. macrophylla in Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the leaf spot pathogen was isolated from H. macrophylla samples, and its pathogenicity was verified based on Koch's that the pathogen could cause a variety of plant diseases. In addition, the incidence of leaf spot disease caused by this pathogen was 10%-20% in Basella alba (Khoo et al, 2022) and 49%-56% in Camellia sinensis (Bao et al, 2019). Furthermore, Zhao et al (2022) reported that E. sorghinum infected H. macrophylla in Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in marginalized communities, distrust of police and concerns of revictimization seem to result in even greater under-reporting of technology-facilitated harms (Aikenhead, 2021; Bailey and Mathen, 2019). At the same time, the criminal law can be “disproportionately enforced against those who are marginalized” (Bailey and Mathen, 2019: 666; Eaton and McGlynn, 2020), resulting in important equality issues regarding the impacts of criminal law and, in practice, creating additional reasons for marginalized communities to avoid relying on criminal responses (Bailey and Mathen, 2019; Dunn, 2021; Khoo, 2021).…”
Section: The Need For Alternative Responses To Tfvbmentioning
confidence: 99%
“…Even when victims do decide to report acts of TFVB, scholars have found that police, prosecutors, and the judiciary can have limited awareness of what laws are applicable to tech-facilitated harms and limited technological literacy, resulting in low rates of successfully investigating and prosecuting these acts (Bailey and Mathen, 2019; Flynn and Henry, 2021; Khoo, 2021; Stevenson-McCabe and Chisala-Tempelhoff, 2021). Additionally, in those rare cases that do result in a successful trial, complainant and community interests may still not be well-served, as the “reactive and punitive” criminal law system is often unable to meet even the basic needs of those impacted by TFVB or address the beliefs that normalize this behavior (Bailey and Mathen, 2019: 695; Dodge, 2021b; Hamilton, 2018; Henry and Witt, 2021; Pennell et al, 2022).…”
Section: The Need For Alternative Responses To Tfvbmentioning
confidence: 99%
See 1 more Smart Citation